Comparative review of One Health and Indigenous approaches to wildlife research in Inuit Nunangat - E. Sudlovenick; E. Jenkins; L. Loseto (One Health)
There is increasing interest in One Health and Indigenous methodologies and approaches in wildlife research, but they are not widely used research applications in the Arctic. Both approaches are wide in scope and originate from different knowledge systems but are often compared synonymously. We review the literature of overlap between the term One Health and Inuit Qaujimajatuqangit (Inuit Indigenous Knowledge) throughout Inuit Nunaat on wildlife research. Three databases (SCOPUS, Web of Science, and BIOSIS) were used to find English language articles and books within the bounds of Inuit Nunaat. While One Health and Inuit Qaujimajatuqangit research approaches share synergies, they are fundamentally disparate owing to their differences in epistemology, including views on the natural environment and wildlife management. We describe current examples of One Health being operationalized in Inuit Nunaat and identify potential to address larger and more complex questions about wildlife health, with examples from terrestrial and marine Arctic wildlife. Both Indigenous methodologies and One Health naturally have a human component at their core, which seamlessly lends itself to discussions on wildlife management, as human actions and regulations directly impact environment and wildlife health.